Integration of The Merdeka Curriculum And The Cambridge Curriculum (Case Study Of An International Class At SMA Batik 1 Surakarta) - Pratiwi, Woro Yustia; Inayati, Nurul Latifatul (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
This research is intended for three things, (1) describe the background to the implementation of the Integration of the Merdeka Curriculum and the Cambridge Curriculum at SMA Batik 1 Surakarta, (2) describe the pattern of implementation of the Integration of the Merdeka Curriculum and Cambridge Curriculum at SMA Batik 1 Surakarta, and (3) understand the implications of the Integration of the Merdeka Curriculum and the Cambridge Curriculum at SMA Batik 1 Surakarta. This research is a qualitative research with a descriptive approach. The research was conducted during PLP (Introduction to School Field) II. The data were obtained through observation and interviews with the curriculum supervisor. The analysis technique is done by collecting data, reducing data, presenting data and drawing conclusions. The results of this research are (1) The background to the implementation of the integration of the Merdeka Curriculum and the Cambridge Curriculum due to future educational needs. (2) Equating student and teacher textbooks with textbooks (in English) in the Cambridge curriculum but not for all subjects, and schools holding courses by bringing in native speakers, as well as facilitating students who wish to take Cambridge certificates. (3) Students have active and passive English language skills, as well as being a school brand that is much in demand today.